Safety and Tolerability of Contezolid Versus Linezolid for Short-Term Treatment of Rifampicin-Resistant Pulmonary Tuberculosis: A Randomized Controlled Study - Wang J; Xue Y; Nie W; Ma L; Chu N; Du Y (Infection and Drug Resistance)
Jun Wang,* Yu Xue,* Wenjuan Nie, Liping Ma, Naihui Chu, Yadong Du Tuberculosis Department, Beijing Chest Hospital, Capital Medical University, Beijing Tuberculosis and Thoracic Tumor Research Institute, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Naihui Chu, Department of Tuberculosis, Beijing Chest Hospital, Capital Medical University, Beijing Tuberculosis and Thoracic Tumor Research Institute, Beijing, People’s Republic of China, Email chunaihui1994@sina.com Yadong Du, Department of Tuberculosis, Beijing Chest Hospital, Capital Medical University, Beijing Tuberculosis and Thoracic Tumor Research Institute, Beijing, People’s Republic of China, Email duyadts@sina.comPurpose: Linezolid is a core drug used to treat rifampicin-resistant tuberculosis (RR-TB) and multidrug-resistant tuberculosis (MDR-TB). However, adverse events (AEs) have limited its clinical application. Safer alternatives to linezolid are needed to address the safety concerns.Patients and Methods: A total of 27 patients with RR-TB (including MDR-TB) were randomly assigned to receive either contezolid (n=14) or linezolid (n=13) in combination with standardized background anti-TB regimens, that is, linezolid-bedaquiline (pyrazinamide)-levofloxacin (moxifloxacin)-cycloserine-clofazimine or contezolid-bedaquiline (pyrazinamide)-levofloxacin (moxifloxacin)-cycloserine-clofazimine. The dosage was 600 mg q12h for linezolid, and 800 mg q12h for contezolid. AE data were collected during the 2-month treatment period to analyze the characteristics, severity, onset time, duration, drug relatedness, management, and outcome of the adverse drug reactions.Results: The median (range) age of contezolid- and linezolid-treated patients was 40.9 (26– 65) and 36.7 (18– 65) years, respectively. The incidence of AEs was 14.3% (2/14) in contezolid-treated patients and 92.3% (12/13) in linezolid group. All drug-related AEs in contezolid group were gastrointestinal reactions (nausea and vomiting one case each). No peripheral neuropathy or myelosuppression AEs were observed. The AEs in linezolid group included anemia (30.8%, 4/13), peripheral neuropathy (53.8%, 7/13), and gastrointestinal reactions (23.1%, 3/13). Dose reduction or discontinuation was required for linezolid in 84.6% (11/13) of patients. The anti-TB efficacy of contezolid and linezolid was comparable in terms of sputum culture conversion rate and imaging-confirmed lesion absorption rate after treatment for 2 months.Conclusion: Contezolid may be a safer alternative to linezolid based on AE incidence in the treatment of multidrug-resistant tuberculosis for two months.Clinical Trial Registration: This study was registered at https://www.chictr.org.cn (identifier: ChiCTR2300074234).Keywords: contezolid, linezolid, safety, multidrug-resistant tuberculosis, peripheral neuropathy, anemia